A Teachers’ Perspective of Digital Technologies In Prison Education - Higgins, Anita (Trinity College (Dublin, Ireland). School of Education, 2021)
ABSTRACT Anita Higgins A Teachers’ Perspective of Digital Technologies In Prison Education Technology and the internet have become an essential part of our daily life in society today. The advantages of online education and the availability of digital tools makes the process of learning and teaching interesting and encouraging now more than ever. Digital technologies have the potential to offer schools, including prison schools enhanced educational support and learning experiences. This dissertation comprises a literature review based on the topics relating to common practices of digital learning in prison education. The literature review investigates some of the ways in which ICT’s and the modernisation of prison infrastructure are being implemented to improve and deliver learning in prisons. It will look at how prisons outside Ireland are making use of digital technologies and how they deal with the same challenges presented while developing digital use in prison education. The dissertation also comprises a mixed research approach that takes shape from the literature reviewed and uses it to survey prison teachers (IT) who teach in prison schools throughout Ireland. The survey was designed to discover if the use of digital technologies in learning is prevalent in Irish prisons from a teacher’s perspective and to also place the Irish prison education system within the global context. The findings of the study suggested digital technologies in prisons demonstrate that it is possible to provide reliable, safe, restricted internet access that widens learning opportunities for individuals in prisons. Digital skills for prisoners are essential for their re-entry to society and prisoners who lack these opportunities are failed. The teaching of new technologies in education has implications for teachers and the findings see a push towards teachers experimenting with newer pedagogical techniques in order to guide and support their students.
Keywords: Science Education; Education